Experiments in co-existence: the science and practices of biocontrol in invasive species management. (August 2015) - Atchison, Jennifer
This paper concerns the science and practices of biocontrol in invasive species management. Although biosecurity scholars have argued for looser, more flexible approaches to securing life, this work is yet to examine how life might be lived where invasive species are entrenched. Here, I bring social and cultural scholarship to bear on ecological and conservation science perspectives quagmired in questions of human intervention and risk, with the purpose of shifting debate toward questions of better care in 'living with' invasive life. Building on Mol's idea of 'tinkering' as embodied and continuous adjustment, and Stenger's approach to experimentation within science, this paper illustrates the practices of biocontrol as experiments in co-existence with invasive life. My empirical focus is invasive plant management in Northern Australia where biocontrol is practiced to manage significant threats to biodiversity from invasive plants. I show that biocontrol practices are diverse and require multiple agencies as well as an acknowledgment of substantial risk. In the ongoing challenge of living with invasive species, the implication is that control is not imposed but can emerge through ongoing embodied and reflexive learning with nonhumans. As experiment, biocontrol is also implicated in the production of new biocommunities—an emerging area requiring further research attention.